TEACHER PERFORMANCE: WHAT IS IT, HOW IMPORTANT IS IT, AND HOW CAN WE MAKE IT HAPPEN SUSTAINABLY? - WONGMAHESAK, Kittisak; Muthmainnah,; KAUR, Dalwinder; CARDOSO, Luís Miguel (Asian Education and Learning Review, 2024)
Teacher performance is critical to educational success, significantly impacting student learning. It is seen as the most crucial school-related factor affecting student achievement. To explore "What is teacher performance? Why is it important? And how can it be sustained?" the authors reviewed literature from the past decade in the Scopus database, finding: 1) Definition: Teacher performance involves a teacher's actions and behavior during teaching, reflecting their professional, personal, and social growth. 2) Importance: Teacher quality is the key to determining student learning more than any other school factor, influencing the success of educational institutions and improving national education systems. 3) Sustainability: Sustaining teacher performance involves prioritizing policy reforms based on teachers' insights and developing a research-driven evaluation system focusing on professional development. In summary, teacher performance is crucial for student achievement, and sustaining it requires policy reforms, effective evaluation systems, and a focus on development rather than control.